On the Exponential Stability of Samuelson Model on Some Classes of Times Scales - Lizama-Yanez, C (Elsevier B.V., 2017)
We prove the remarkable property that the exponential stability of the Samuelson model is invariant under the times scales R and hZ whenever 0<h≤1. We characterize the domains of stability for these time scales and we also give sufficient conditions for stability on a class of mixed times scale. We prove analogous results for the Samuelson model in an open economy. Our methods are based on a spectral characterization of exponential stability due to Potzsche, Siegmund and Wirth and a multiplier accelerator model on time scales due to Bohner, Gelles and Heim. © 2017 Elsevier B.V.